2017
DOI: 10.1002/stem.2642
|View full text |Cite
|
Sign up to set email alerts
|

PRMT8 Controls the Pluripotency and Mesodermal Fate of Human Embryonic Stem Cells By Enhancing the PI3K/AKT/SOX2 Axis

Abstract: Basic fibroblast growth factor (bFGF) supplementation is critical to maintain the pluripotency of human pluripotent stem cells (hPSCs) through activation of PI3K/AKT, rather than MEK/ERK pathway. Thus, elaborate molecular mechanisms that preserve PI3K/AKT signaling upon bFGF stimulation may exist in hPSCs. Protein arginine methyltransferase 8 (PRMT8) was expressed and then its level gradually decreased during spontaneous differentiation of human embryonic stem cells (hESCs). PRMT8 loss- or gain-of-function stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 58 publications
0
22
0
1
Order By: Relevance
“…MiR-200 was found to have both direct and indirect mechanisms of targeting CXCL1 to inhibit cancer angiogenesis [26]. In an experimental animal model, after co-injection of CXCL1 with human adipose-derived mesenchymal stem cells (hADSCs), hADSCs promoted residual BC proliferation and metastasis via the PI3K/AKT/SOX2 axis [27]. CXCL2 shares 90% amino acid homology with CXCL1.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-200 was found to have both direct and indirect mechanisms of targeting CXCL1 to inhibit cancer angiogenesis [26]. In an experimental animal model, after co-injection of CXCL1 with human adipose-derived mesenchymal stem cells (hADSCs), hADSCs promoted residual BC proliferation and metastasis via the PI3K/AKT/SOX2 axis [27]. CXCL2 shares 90% amino acid homology with CXCL1.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction results in the enhancement of AKT activity instead of the MEK/ERK pathway. PRMT8/PI3K/AKT axis maintains pluripotency of hESC as well as mesodermal differentiation via the regulation of Sox2 (Jeong et al, 2017). In a recent study, Haghighi et al (2018) showed that among the downstream mediators of FGF2 signaling pathways, the MAPK pathway plays a pivotal role in maintaining the pluripotency of hiPSCs.…”
Section: Fgf2mentioning
confidence: 99%
“…These various interdependencies between PI3K/AKT and SOX2, detected across a spectrum of different malignant and healthy (stem) cell types, have led to the notion of an independent PI3K/AKT/SOX2 signaling branch that diverges from the canonical PI3K/AKT/mTORC1 axis (see refs. [100,101] and Fig. 2 for schematic illustration).…”
Section: Intertwined Relationships Between Pi3k/akt Signaling and Soxmentioning
confidence: 99%